The influence of plant growth regulators and light supply on bitter cassava callus initiation for starch production - Mohamad Puad, Noor Illi; Ibrahim, Soumayat Ali; Azmi, Azlin Suhaida; Abduh, Muhammad Yusuf (IIUM Press, 2024)
The application of cassava starch in the biopolymers industry has been growing significantly due to its low cost, good oxygen barrier in the dry state, and biodegradability. Plant culture technology is an alternative to traditional propagation as it does not require large areas for production, has a higher rate of multiplication, and produces disease-free plants. However, the application of cassava callus culture for starch production is limited. This study focuses on identifying the significant culture parameters for a maximum Rayong cultivar cassava callus growth and evaluation of its starch content. Cassava stems petiole and leaf explants were cultured on MS medium containing different combinations of 2,4-D (8, 12, and 15 mg/L) and BAP (1, 3, and 5 mg/L) under three light conditions (0, 16, and 24 h). The screening of the most influential parameter was done using the 2-level Factorial Design in Design Expert v13 by analyzing the frequency of callus formation. All leaf explant turned brown with no callus induction. The highest frequency of callus formation derived from stem petiole explant was achieved by the combination of 8 mg/L 2,4-D and 1 mg/L BAP under the light condition (75%) followed by 8 mg/L 2,4 D + 1 mg/L BAP under the dark condition (50%). Based on the ANOVA analysis, the individual supply of 2,4-D and BAP respectively, have a negative effect on callus formation while the combination of 2,4-D and BAP has a positive effect. Light supply did not significantly affect cassava callus formation. The amount of starch in the cassava callus was then investigated using an iodine test which yielded 0.21% of the total weight of the callus (0.0101g). The amount of starch is relatively low considering that the callus was not grown under the optimum condition for starch production. The findings of this study open prospects for future research in cassava cultures in favor of starch production.